Pulse Plasma-Chemical Synthesis of Ultradispersed Powders of Titanium and Silicon Oxide - Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna (2013, 2013)
Title screen